2020
DOI: 10.1007/s10900-020-00870-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Perceptions and Related Factors Concerning COVID-19 Epidemic in Chongqing, China

Abstract: Objective To assess perceptions of risk and related factors concerning COVID-19 epidemic among residents in Chongqing city, China. Methods With convenience sampling, a web questionnaire survey was conducted among 476 residents living in Chongqing on February 13rd to 14th in 2020, when citizens just started to get back to work. Results Residents' estimated perceived risks were (4.63 ± 0.57), (4.19 ± 0.76), (3.23 ± 0.91) and (2.29 ± 0.96) for the infectivity, pathogenicity, lethality and self-rated infection pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
79
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 15 publications
13
79
5
1
Order By: Relevance
“…Bearing in mind that the elderly population are at greater risk of death [6,44], it is notable that this group, to a lesser degree, also has a high risk perception. These results are in line with the findings of Barber and Kim [25], in which they explain how elder adults report less concern and present less anxiety over health than younger adults; and they contradict other studies which determine that the elderly are one of the groups with a higher perception of threats [36,45].…”
Section: Influence Of Socio-demographic Variables On Risk Perceptionsupporting
confidence: 83%
See 1 more Smart Citation
“…Bearing in mind that the elderly population are at greater risk of death [6,44], it is notable that this group, to a lesser degree, also has a high risk perception. These results are in line with the findings of Barber and Kim [25], in which they explain how elder adults report less concern and present less anxiety over health than younger adults; and they contradict other studies which determine that the elderly are one of the groups with a higher perception of threats [36,45].…”
Section: Influence Of Socio-demographic Variables On Risk Perceptionsupporting
confidence: 83%
“…At that time, there were 7753 cases diagnosed in Spain, with a mortality rate of 3.7% of confirmed cases (Ministry of Health update No. 45).…”
Section: Introductionmentioning
confidence: 99%
“…the majority are not worried that they themselves or their family member may be infected by the virus. Our nding does not match with previous studies which state that people are worried about getting infected by COVID-19 8 . According to our study, people think that getting infected by COVID-19 cannot be serious, this may be because the majority of our participants were of age group 20-40 and the symptoms of corona are not too severe in the young age…”
Section: Discussioncontrasting
confidence: 99%
“…Scholars have argued that COVID-19 is a risk that is "unfamiliar, invisible, dreaded, potentially endemic, involuntary, and disproportionally impacts vulnerable populations such as the elderly" (Chakraborty, 2020, p.1). Since the start of the pandemic researchers around the world have begun to investigate the determinants of risk perceptions of COVID-19 (e.g., Abdel Wahed et al 2020; Bruine de Bruin, Saw, and Goldman 2020; Ding et al 2020;Dryhurst et al 2020;He et al 2020;Karasneh et al 2021;Liu, Zhang, and Huang 2020;Mertens et al 2020;Qian and Li 2020;Shao and Hao 2020;Zhong et al 2021). Perhaps the largest comparative international study of risk perception is reported by Dryhurst et al (2020), who found that across ten countries in Europe, America, and Asia people's personal experience with the virus, their individualistic and prosocial values, trust in government, science, and medical professionals as well as a sense of personal and collective efficacy were among the most important predictors of people's holistic perception of the risk of COVID-19 (Dryhurst et al 2020).…”
Section: Introductionmentioning
confidence: 99%